Structural parameters optimization for enhanced sealing performance of soluble ball seat sealing ring in shale gas volume fracturing process - Shuang Jing; Anle Mu; Zhen Chen; Qingjie Ran; Deyong Luo; Tao Xiong (PLoS ONE, 2025)
In the volumetric fracturing process of tight oil and gas horizontal wells, the soluble ball seat emerges as a crucial tool for pressure sealing due to its rapid solubility, full-diameter production capacity, and straightforward construction process. This study focuses on enhancing the sealing efficacy of metal sealing rings paired with soluble ball seats. Employing finite element analysis, structural optimization, and indoor diameter reduction tests, we assess the sealing performance of metal sealing rings fabricated from traditional Al-Mg alloy (Material 1) and a modified Al-Mg/Ga alloy (Material 2). By establishing a comprehensive evaluation system for the sealing performance and utilizing finite element simulation, we compare the mechanical properties and sealing effectiveness of both materials during the setting process. Our findings reveal that Material 1’s sealing ring endures stresses surpassing allowable limits, heightening the risk of local failure. Conversely, structural optimization of the Material 2 sealing ring allows for safe installation under a standardized 5T setting force, ensuring that contact stress between the sealing ring, casing inner wall, and the sliding body exceed the fracturing fluid pressure with a relatively uniform stress distribution. Subsequent indoor diameter reduction tests verify the superior safety performance of Material 2 over Material 1, aligning with the finite element analysis outcomes. Collectively, this research delineates how finite element analysis, structural optimization, and empirical tests augment the structural safety and sealing functionality of metal sealing rings for soluble ball seats, furnishing a basis for refining the design of soluble ball seat sealing rings.